2020
DOI: 10.17816/nb34054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional characteristics of remission and rehabilitation of patients with schizophrenia

Abstract: The aimof this study was to evaluate real social functioning of patients in remission of paranoid schizophrenia in the dynamics of treatment and rehabilitation measures. Methods.Patients of the medical rehabilitation department were included in the transverse clinical and population study. Clinical scale evaluation was used, including PANSS, PSP. Results.It was shown that patients with schizophrenia included in the program of therapeutic and rehabilitative measures, met clinical and functional crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The concept of “practical recovery” remains ambiguous — this is just the disappearance of the symptoms of the disorder without complete restoration of mental functions or “new health’, as described by Kondratiev (2010) [ 29 ]. It is important to note that despite more than a half century of research, remission in schizophrenia remains poorly described in practical psychiatry [ 122 , 123 , 124 , 125 ]. It is stated both in Russian and foreign studies that so-called psychosocial remissions are observed in no more than 15% of patients [ 35 , 122 , 123 , 124 , 125 , 126 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of “practical recovery” remains ambiguous — this is just the disappearance of the symptoms of the disorder without complete restoration of mental functions or “new health’, as described by Kondratiev (2010) [ 29 ]. It is important to note that despite more than a half century of research, remission in schizophrenia remains poorly described in practical psychiatry [ 122 , 123 , 124 , 125 ]. It is stated both in Russian and foreign studies that so-called psychosocial remissions are observed in no more than 15% of patients [ 35 , 122 , 123 , 124 , 125 , 126 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that despite more than a half century of research, remission in schizophrenia remains poorly described in practical psychiatry [ 122 , 123 , 124 , 125 ]. It is stated both in Russian and foreign studies that so-called psychosocial remissions are observed in no more than 15% of patients [ 35 , 122 , 123 , 124 , 125 , 126 ]. Potapov et al (2010) [ 127 ] note that symptomatic remission is possible for about 20% of patients if modern therapy is administered (in compliance with international criteria).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation